THE BOUNDARIES OF SHARENTING IN FAMILY VLOGS: AN ANALYSIS OF FIQH HADHANAH AND THE CHILD PROTECTION LAW - Burhanuddin Aziz Ar Rasyid; Khoirul Ahsan (Journal Analytica Islamica, 2026)
Sharenting practices on family-vlogging YouTube channels have expanded the sphere of child-rearing from the private domain of the family into the digital public sphere. This study formulates ethical boundaries for sharenting among Muslim families by integrating the Islamic jurisprudence of ḥaḍānah, maqāṣid al-sharīʿah, and the Indonesian Child Protection Law. Content analysis was conducted on 40 publicly accessible videos purposively selected from four YouTube channels published between 2024 and 2026. A total of 152 scenes were subsequently assessed through doctrinal legal analysis based on maṣlaḥat al-maḥḍūn, the prevention of harm, maqāṣid al-sharīʿah, and statutory provisions concerning child protection. The study identifies three typological categories: documentary content comprising 75 scenes, emotional exposure comprising 47 scenes, and commercial content comprising 30 scenes. Documentary content carries the risk of creating a persistent and traceable digital record of children’s lives, whereas emotional exposure requires particular restrictions when children’s illness, fear, embarrassment, or private experiences are transformed into public narratives. Commercial content requires careful assessment of its benefits, the burden of content production imposed on children, and the availability of meaningful opportunities for children to refuse participation. This study positions the jurisprudence of ḥaḍānah as an evaluative framework, maqāṣid al-sharīʿah as an instrument for balancing risks and benefits, and the Child Protection Law as a positive legal framework. Its principal contribution lies in proposing precautionary guidelines and a pre-upload assessment mechanism without making determinations regarding specific legal violations.